The Influence of Digital Marketing and Service Quality on Purchase Decisions in MSMEs: The Role of Buying Interest as a Mediation Variable and Brand Image as a Moderation Variable - Nanik Wahyuningtiyas; Imam Mukhlis (Cita konsultindo, 2024)
This study investigates the impact of digital marketing and service quality on consumer purchase decisions in MSMEs, examining purchase intention as a mediating variable and brand image as a moderating variable. The research aims to provide a comprehensive understanding of how these factors interact to influence purchasing behavior within digital environments for micro, small, and medium enterprises. A quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed, with data collected from 279 respondents who engaged with digital marketing content of MSMEs. Results reveal that digital marketing significantly enhances purchase intention, as does service quality, indicating the importance of these factors in cultivating consumer interest. Purchase intention further mediates the relationship between digital marketing, service quality, and purchase decision, underscoring its role as a critical step in converting interest into action. However, brand image showed limited moderating effects, suggesting that its influence may vary depending on the presence of other strong predictors like direct engagement and service quality. These findings contribute to the theoretical understanding of consumer decision-making in the context of MSMEs and provide practical insights for small business owners aiming to optimize their digital strategies. The study highlights the need for marketers within MSMEs to focus on enhancing purchase intention through digital marketing and service quality efforts, which can effectively drive purchase decisions in competitive, technology-driven markets.